La cooperación internacional para el desarrollo y la protección de los derechos humanos de las personas LGTBI: una mirada desde la Agenda 2030 - Sergio Colina-Martín (Revista Iberoamericana de Estudios de Desarrollo)
The Sustainable Development Goals provide new grounds for a stronger interlinkage between international cooperation and development agendas and the protection and promotion of the human rights of LGBTI persons. The 2030 Agenda’s commitment to leave no-one behind provides a clear mandate for all countries and public actors, including development agencies, to put equality, inclusion and non-discrimination at the center of international cooperation policies, in the framework of a human rights-based approach. With this paper, it is intended to analyze the most meaningful intersections between sustainable development goals and targets and the rights of LGBTI persons from a general perspective and suggest possible ways forward. In the study, it is also considered the characteristics of the Spanish cooperation’s approach in this regard, from a historical point of view, and present the latest developments.